The Dimension of Presupposition in the Prose Discourse of Sheikh Al-Waeli - Hassan Qasim , Assist. Lect . Qaisar; Sadiq Ghalib, Prof. Dr. Jasem (Basra studies journal, 2025)
This study explores the concept of presupposition as a pragmatic phenomenon that plays a key role in meaning construction of discourse, focusing specifically on the prose discourse of Dr. Ahmed Al-Waeli, one of the most prominent contemporary preachers of the Hussaini pulpit. . The research begins with a theoretical overview of presupposition, outlining its types and pragmatic functions. It then moves to a practical analysis based on selected excerpts from Al-Waeli’s speeches, aiming to uncover the most frequent presuppositions embedded in his discourse and assess their role in achieving persuasion and effective communication. The analysis reveals that Al-Waeli employs presuppositions with rhetorical awareness, using them to build common ground with his audience—thereby enhancing the persuasive power and communicative depth of his discourse.